ANALISIS DAYA HIDUP DAN PERTUMBUHAN BENIH BIJI MARGA Shorea ROXB. EX C.F.GAERTN. DI PERSEMAIAN - Ihsan Fawzi, Nurul (Wahana Forestra: Jurnal Kehutanan, 2019)
Deforestation in Kalimantan island made 17 million hectares of primary forest loss in the last 40 years. The forest restoration project needs native species seedlings from the previous tree on the damaged forest. The aim of this study to determine the germination and growth of the types of Shorea obtained from TNGP. This study used 38,728 seeds from four species of the Shorea genus: red meranti (Shorea leprosula), Tengkawang (Shorea macrophylla), white meranti (Shorea agami), and belabak (Shorea quadrinervis) obtained from forests near reforestation sites. The result show the average germination rate is 80%. The highest germination rate from the Shorea quadrinervis was 98.7%. We found that the growth of the Shorea genus from seeds was ready for planting in a period of 4 - 5 months.